Motif dan Makna Penggunaan Bahasa “Jaksel” Di Kalangan Mahasiswa Pengguna Bahasa “Jaksel” Dalam Kehidupan Sehari-hari - Brahma Wicaksono; Siti Nursanti; Wahyu Utamidewi (Peneliti.net, 2022)
The use of language by children born in the 90s to 2000s seems to have led to a shift towards modernism. In recent years, a new trend has emerged for the